Sensorimotor coordination aftereffects of exposure to a virtual environment - Harm, Deborah L.; Taylor, Laura C.; Reschke, Millard F.; Somers, Jeffrey T.; Bloomberg, Jacob J. (The Visual computer, 2008)
Virtual reality environments (VRs) offer unique training opportunities, particularly for training astronauts and preadapting them to microgravity. The purpose of the current research was to compare disturbances in eye–head–hand (EHH) and eye–head (GAZE) sensorimotor coordination produced by repeated exposures to VR systems. In general, we observed significant increases in position errors in manual target acquisition for both horizontal and vertical targets. We also observed a significant decrement in the ability of subjects to maintain gaze on horizontal eccentric targets immediately after exposure to VR. These preliminary findings provide some direction for developing training schedules for VR users that facilitate adaptation and support the idea that VRs may serve as an analog for sensorimotor effects of spaceflight.